Management of acute intracerebral haemorrhage – an update - Law, Zhe Kang; Appleton, Jason P.; Bath, Philip M.W.; Sprigg, Nikola (Royal College of Physicians, 2017)
Managing acute intracerebral haemorrhage is a challenging task for physicians. Evidence shows that outcome can be improved with admission to an acute stroke unit and active care, including urgent reversal of anticoagulant effects and, potentially, intensive blood pressure reduction. Nevertheless, many management issues remain controversial, including the use of haemostatic therapy, selection of patients for neurosurgery and neurocritical care, the extent of investigations for underlying causes and the benefit versus risk of restarting antithrombotic therapy after an episode of intracerebral haemorrhage.